Leadership Training in African Independent Churches–Working with Whites - Lagerwerf, Leny (Exchange, 1994)
This paper draws attention to the fact that since the beginning of the 1960s white missionaries from mainline churches have become involved in the training of leaders and ordinary members of African independent churches (AICs). In many cases, however, leaders of AICs remain suspicious of missionaries who offer to come and assist them. Therefore a number of questions come to the fore: How did the relationships between mainline churches and AICs start? What were the motives on either side? What kind of programmes were elaborated? Were there specific problems in the relationships? The author deals with these questions in three case studies - Fambidzano (Zimbabwe), Mennonite Ministries all over Africa, and the Church of Jesus Christ on Earth through the Prophet Simon Kimbangu (EJCSK) - focusing on theological training. She concludes, amongst others, that the relation between the two parties remained a delicate one; that there may be a sensitiveness on the side of the AICs as to certain doctrinal and pastoral subjects in the curriculum; that all churches were positive about other subjects, like bible study and church history; that financial assistance may lead to tensions; and that the aim of bridge-building between AICs themselves or between AICs and the mainline churches was supported by all, though in practice it was not always easy. Notes, ref.
Free
Keywords: African Independent Churches Conference; Kimbanguism; Leadership; Religious – Christianity; Mennonites – Missions; Peer reviewed; Race relations and church